Does regional innovation policy really work for Industry 4.0? Evidence for industrial districts (2023)
Industry 4.0 threatens established lock-in paradigms in some districts. In this study, we compare different innovation policies aimed at facilitating Industry 4.0 awareness and its adoption in three Marshallian Industrial Districts (MIDs), asking: ‘What’ types of innovation policies work for Industry 4.0 in industrial districts? And, where they do, ‘how’ are those innovation initiatives designed, developed and implemented for digitizing districts? Using qualitative evidence based on 24 interviews and the review of existing literature concerning Industry 4.0 in three MIDs, results show different mechanisms and approaches for creating awareness and maximizing the diffusion of Industry 4.0 in each district, as a result of each local ‘cognitive structure’. One size-fits-all policies are not realistic for digitization: collective actors leading place-based collective actions that are bottom-up and co-designed with public and private local actors is what works best. For policymakers, this study presents guidance for developing Industry 4.0 in MID settings.